A Case Study in JML-Assisted Software Development - Cataño, Néstor; Barraza, Fernando; García, Daniel; Ortega, Pablo; Rueda, Camilo (Electronic notes in theoretical computer science, 2009)
This paper presents a case study in formal software development of a plugin for a Java Desktop project management application using JML. Our goals for the case study include determining how JML-based formal methods can be incorporated in traditional software engineering practices used in the software industry and how the use of JML for modeling software requirements can enforce the programming of correct Java code. We demonstrate how JML-based formal methods can be used so as to effectively contribute to the making of decisions within a software development team.